Investigation on the radioactive wastes disposals - Chin, Christopher Wei Zhong. (2012)
In recent years many countries have taken a step into nuclear power generation as an alternative to our depleting natural resources. There has also been much advancement in nuclear medicine in recent years. However, with these advancements new problems start to arise. Nuclear power generation, nuclear medicine and the other applications of nuclear technology (e.g. weapons and research) all generate radioactive wastes that are hazardous to most forms of life and the environment. Thus, these wastes need to be disposed of carefully to prevent damage to life and the environment.